Nietzsche : an approach - Lavrin, Janko, 1887-1986 (Routledge library editions. Friedrich Nietzsche, 2009)
Janko Lavrin's influentialÈbiography of Friedrich Nietzsche, originally published in 1948, analyses the bond between Nietzsche's personal fate on the one hand and the trend of his thought on the other, set against the background of contemporary crisis typicalöf mankind in general.